Age-related thinning of orbicularis oculi muscle inside upper eyelid and its possible association with sunken upper eyelids - Takamasa Gomi; Itsuko Okuda; Ami Seino; Kaho Ohara; Yasuko Harada (Scientific Reports)
Abstract Sunken upper eyelid is a morphological symptom that surrounds the eye with aging; however, its causes remain poorly understood. We investigated the correlations between the sunken upper eyelid and morphological parameters inside the eye area using magnetic resonance imaging (MRI), verified the relationship between age and degree of sunken upper eyelid photographically, and quantified muscle fibers histologically classified by myosin heavy chain (MYH) species and connective tissues in the superior palpebral part of the orbicularis oculi muscle from cadaveric specimens of various ages. The results showed the development of sunken upper eyelids, decreased thickness and number of MYH4-positive muscle fibers, and increased collagen and elastic fiber proportions in the orbicularis oculi muscle with age. On MRI, both the thickness of the orbicularis oculi muscle and the vertical position of the globe within the orbit were negatively correlated with the sunken upper eyelid. Changes in the orbicularis oculi muscle offer new insights into the mechanisms underlying age-related morphological changes in the periocular area.